2018
DOI: 10.1302/2046-3758.77.bjr-2018-0043.r1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of local antibiotic prophylaxis when treating open limb fractures

Abstract: ObjectivesAs well as debridement and irrigation, soft-tissue coverage, and osseous stabilization, systemic antibiotic prophylaxis is considered the benchmark in the management of open fractures and considerably reduces the risk of subsequent fracture-related infections (FRI). The direct application of antibiotics in the surgical field (local antibiotics) has been used for decades as additional prophylaxis in open fractures, although definitive evidence confirming a beneficial effect is scarce. The purpose of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 50 publications
1
95
0
6
Order By: Relevance
“…Local antibiotics may be particularly effective in chronic/late onset infections, where the perfusion of systemic antibiotic is greatly reduced due to chronic tissue scarring. A recent systematic review [76] of contaminated open fracture wounds showed a considerable risk reduction if additional local antibiotics were applied. Although PMMA was the most studied material, the prophylactic effect of absorbable carriers for local antibiotic delivery showed also promising results [76].…”
Section: Local Antimicrobial Therapy and Dead Space Managementmentioning
confidence: 99%
“…Local antibiotics may be particularly effective in chronic/late onset infections, where the perfusion of systemic antibiotic is greatly reduced due to chronic tissue scarring. A recent systematic review [76] of contaminated open fracture wounds showed a considerable risk reduction if additional local antibiotics were applied. Although PMMA was the most studied material, the prophylactic effect of absorbable carriers for local antibiotic delivery showed also promising results [76].…”
Section: Local Antimicrobial Therapy and Dead Space Managementmentioning
confidence: 99%
“…The drug of choice for local treatment has been pearl gentamicin, tobramycin and vancomycin; currently on the market are present many formulations, some of them are combinations with osteoinduction molecules. It has been observed a reduction by 11.9% of the risk of infection when local therapy has been added to certain wounds [41].…”
Section: Primary Surgical Managementmentioning
confidence: 99%
“…Das beinhaltet u. a. konsequente und ggf. wiederholte chirurgische Débridements, die Applikation von lokalen und systemischen Antibiotika, temporären Wundverschluss und andere Maßnahmen [10,11,20].…”
Section: Infektionunclassified
“…Motorisierte intramedulläre Verlängerungsnägel in Kombinationen mit anderen Entwicklungen und Fortschritten der muskuloskeletalen und Weichteilchirurgie haben die Möglichkeiten der rekonstruktiven Chirurgie in zahlreichen Bereichen stark erweitert, die bislang der externen Fixation vorbehalten waren [9][10][11][12].…”
unclassified